Hydrated lime matrix decreases ruminal biohydrogenation of flaxseed fatty acids - C.A. Alvarado; C.C. Aperce; E. Van Cleef; K.A. Miller; C.L. Van Bibber-Krueger; F. Scarpino; D. Klamfoth; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2013)
Omega-3 fatty acids are essential nutrients for humans, but dietary intake of these nutrients by many Americans is inadequate due to low consumption of omega-3-rich foods such as fish, walnuts, and flaxseed. In contrast, per capita consumption of red meat is relatively high, but these products normally contain only small amounts of omega-3 fatty acids. Feeding cattle diets that contain omega-3 fatty acids has consistently increased the proportion of the desirable fats that accumulate in beef. Unfortunately, the proportion of dietary omega-3 fats that are deposited into beef tissues is relatively low, because microorganisms within the rumen biohydrogenate the unsaturated omega-3 fatty acids extensively to produce the saturated fats that are characteristic of beef fat. Encapsulation of fats has been proposed as a method for improving efficiency of transfer of omega-3 fats into beef. Encapsulation processes apply a protective barrier on the surface of fats or fat-containing feeds, which theoretically decreases fats' susceptibility to microbial biohydrogenation. Protective coatings must remain intact to retain their functionality, and physical damage to the coatings that occurs with normal handling can result in poor efficacy because the core material is exposed to microorganisms in the rumen. Embedding feed particles within a homogeneous protective matrix constitutes a potentially useful alternative to protective surface barriers. The matrix is created by mixing feed particles that are to be protected with a suitable matrix material that is resistant to microbial digestion and subsequently forming the mixture into pills. In cases where physical damage occurs, exposure of the core material is confined to the broken surface, and the remainder of the matrix retains its ruminal stability. The objective of this study was to determine if embedding flaxseed within a matrix of hydrated dolomitic lime could be used as a method to decrease biohydrogenation of polyunsaturated omega-3 fatty acids, thus improving efficiency of omega-3 fatty acids absorption into the bloodstream.
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-162-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1083; Cattle; Hydrated lime matrix; Flaxseed; Fatty acid; Biohydrogenation; Omega-3 fatty acid